2015
DOI: 10.1108/hff-03-2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional flow of an Oldroyd-B fluid with Newtonian heating

Abstract: Purpose – The purpose of this paper is to analyze the boundary layer flow of an Oldroyd-B fluid with Newtonian heating. Design/methodology/approach – Series solutions are found by homotopy analysis method. Findings – Temperature profile increases with an increase in conjugate parameter. Increase in parameter β and Prandtl number Pr decreases the temperature profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The effects of thermal radiation and variable thermal conductivity on MHD three dimensional on three dimensional viscoelastic fluid flow was discussed by Shehzad et al [7]. Ramzan et al [8] explored three dimensional Oldroyd-B fluid under the influence of Newtonian heating. Shehzad et al [9] examined Magneto hydrodynamic three dimensional flow of Jeffrey fluid with Newtonian heating.…”
Section: Introductionmentioning
confidence: 98%
“…The effects of thermal radiation and variable thermal conductivity on MHD three dimensional on three dimensional viscoelastic fluid flow was discussed by Shehzad et al [7]. Ramzan et al [8] explored three dimensional Oldroyd-B fluid under the influence of Newtonian heating. Shehzad et al [9] examined Magneto hydrodynamic three dimensional flow of Jeffrey fluid with Newtonian heating.…”
Section: Introductionmentioning
confidence: 98%
“…Farooq et al [30] analyzed the MHD convective flow of Jeffrey fluid with Newtonian heating. Ramzan et al [31] examined the 3-dimensional convection of an Oldroyd-B-type fluid over a stretching sheet with Newtonian heating. The characteristics and influences of Newtonian heating in stagnation flow and free stream velocity of a Burgers fluid is reported by Hayat et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the term Newtonian heating was introduced by Merkin 14 . Later, such kind of heating conditions were effectively used by a number of authors, for example, Ramzan et al, 15 Muhammad et al, 16 and Uddin et al 17 in simulations of polymeric and magnetic material flow. These investigations showed that altogether different and better outcomes are accomplished to Newtonian limit conditions for warming contrasted and convectional warm divider conditions.…”
Section: Introductionmentioning
confidence: 99%